Analisis Tingkat Kesehatan PT.Bank Negara Indonesia Tbk. Melalui Pendekatan Earnings dan Capital Periode 2014-2018 - Harie Pratama; Hamid Halin; Endah Dewi Purnamasari (Jurnal Bisnis, Manajemen, dan Ekonomi, 2022)
This study aims as to analyze the bank financial health rates of PT Bank Negara Indonesia, Tbk. for the period of 2014 to 2018. Data were collected through documentation and analyzed employing the earnings and capital approach using the indicators of return on asset (ROA), net interest margin (NIM), and cash adequacy ratio (CAR). The results unveil that during 2014 to 2018 respectively: (1) the earnings aspects of PT Bank Negara Indonesia, Tbk. were rated highly healthy with an average ROA value of 3.37 percent, 2.48 percent, 2.57 percent, 2.62 percent, 2.58 percent and NIM of 4.79 percent, 4.77 percent, 4.28 percent, 3.43 percent, 3.20 percent; (2) the capital aspects were rated highly healthy with an average CAR value of 16.27 percent, 17.90 percent, 18.78 percent, 18.42 percent, and 18.03 percent; (3) overall earnings and capital aspects at PT Bank Negara Indonesia, Tbk. from 2014 to 2018 were in the composite rank 1 (PK 1) which was highly healthy